The Effect of Return on Asset, Earning per Share, Price Earnings Ratio, BI-Rate on Sharia Stock Prices Listed on Jakarta Islamic Index 70 - Widyaningrum, Lina; Andni, Riyan (Unisia, 2024)
This study analyzes the effect of return on assets, earnings per share, price earnings Ratio and BI-Rate on the price of Shari’ ah shares in a managed company included in the Jakarta Islamic Index 70 (JII 70). Sampling using the Purposive Sampling technique by looking at data from quarterly financial statements for the period March 2018 to December 2022 obtained six samples of companies in the consumer goods sector. This includes quantitative research using documentation methods and literature sourced from secondary data. using fixed-effect estimation models and panel data regression analysis methods, with a chow test, Hausman test, classical assumption test, and hypothesis test, where data processing was performed using Eviews. The results showed that ROA and PER affected stock prices, while PER and BI-Rate did not have a partial effect on stock prices. Simultaneously, ROA, EPS, PER and BI-7day can affect stock prices. Thus, a definite investor decision can be made regarding the stock when the factors meet the accepted yield criteria. However, it is necessary to conduct further research on the relationship of factors in understanding market conditions that are indicators in investment decisions to be more relevant and obtain benefits in the future.